Sexual and Affective Consent from the Voices of Female Higher Education Students in Chile - Brito Rodríguez, Sonia; Basualto Porra, Lorena; Posada Lecompte, Margarita (Última Década, 2023)
The article problematizes emotional and sexual consent from the voices of women Chilean students of higher education. To do this, qualitative research is conducted that analyzes their narratives on sexual violence and femicide, shared in the discussion groups. The main results show that female students feel violated in their private and public contexts, since in the patriarchal culture forms and styles of relationship are naturalized that make invisible and undermine the consent of young women, feeling, moreover, that the danger of suffering violence is narrowed to family, academic and sexual-affective spaces.